A configuração constitucional da acessibilidade e sua influência na propriedade imobiliária: a acessibilidade como parte do conteúdo jurídico da função social da propriedade - Maia, Maurício (2018)
The Brazilian Federal Constitution has in equality and human dignity two of its main vectors of interpretation and application. Combined with the fundamental objectives of the Republic, these two values give rise to a constitutional commandment of inclusion, imposing on the State and the society the duty to enable all people, without exception, to participate fully and effectively in social life, on an equal footing opportunities. Also, in order to achieve this, it is necessary to identify groups of people who need special legal treatment so that they can have the same opportunities of participation as other people. One of these groups of people is the group of people with disabilities. A fundamental part of this differentiated juridical treatment granted to persons with disabilities is the accessibility, a fundamental right which is instrumental to all other rights to be exercised by the members of this group of persons. Accessibility currently has a comprehensive concept, and is an important instrument for eliminating barriers to the inclusion of people with disabilities, interacting with other fundamental rights, such as the right to property. The guarantee of accessibility necessarily goes through the configuration that the legal system assigns to the property. We can understand that the accessibility is an integral part of the social function that the property must comply, by express constitutional determination. In this sense, there is a duty set by the constitutional order of observance of the norms of accessibility in the existing buildings or in the buildings that will be constructed. In the case of existing buildings, according to their nature, there is a duty of adaptation, which non-compliance may give rise to the consequences for non-compliance with the social function of property, as well as the responsibility of public or private agents. Public officials may even be held liable for acts of administrative misconduct, thus demonstrating the relevance of the accessibility in the Brazilian legal system